Effectiveness of Rehabilitation Programs for Child Trafficking Victims in Indonesia - Raden Ajeng Diah Puspa Sari; Dr. R. Rahaditya, S.H., M.H (Dinasti Research, 2024)
Child trafficking is a type of crime that significantly impacts victims' lives, causing physical, mental, and social trauma. Rehabilitation programs are essential to help child trafficking victims recover and continue their lives. These programs are designed to meet various victim needs, including psychological recovery, physical health, education, and social reintegration. However, many question the effectiveness of these rehabilitation programs, particularly regarding victims' specific needs, available support levels, and how well they help victims readapt to society. The focus of this research is to evaluate the effectiveness of rehabilitation programs offered to child trafficking victims in Indonesia. These programs are expected to address the deep trauma experienced by victims, improve physical health impaired by exploitation, and provide necessary support and skills for social and economic reintegration. However, field evidence shows that many problems arise during program implementation. These include resource limitations, victims' lack of access to mental health services, and insufficient cooperation between relevant agencies managing rehabilitation.